PEMULIHAN KONDISI REMAJA KORBAN NARKOBA MELALUI PENDEKATAN KONSELING - DARIMIS DARIMIS (Ta'dib, 2010)
Drug abuses among teenagers increase from day to day. In the last decade, the number of victims of the drugs endangers the existence of the nation in the future. Such reality should be responded through concrete, anticipative, and soluble efforts to avoid physical, psychological, social, moral and religious destructions. One of those efforts is through counseling approach by strengthening perception, attitude, understanding and commitment to enhance holistically healthy life style. Such counseling services as individual and group counselings, family counseling and religion-based counseling can be used for the condition recovery of the drug abused teenagers.Kata kunci: pemulihan,  kondisi remaja, korban narkoba, pendekatan konseling